The first medical textbooks published after the founding of the Medical School in Belgrade - Jović, Pavle (Srpski arhiv za celokupno lekarstvo, 2002)
After the founding of the University Medical School in Belgrade in 1920 the most urgent necessity was to write the first textbooks for theoretical medical studies. However, the first published textbook was that for forensic medicine (one of the last subjects in the study of medicine). This was the textbook "Forensic Medicine" written by military physician and internist Svetozar Peshitsh (1880-1936) in Belgrade in 1921. Next year the "Technique of Autopsy" was published. The author was Milovan Milovanovitsh (1893-1948), forensic physician. In 1923 there were published two medical textbooks for students of medicine: "Fundamental Basis for Human Anatomy" written by Russian physician Ilja Shapshal (1878-1949) and "Histological Techniques" written by the founder of histology at the Medical School in Belgrade, Aleksandar Dj. Kostitsh (1893-1983).